The anthropology of religion : an introduction - Bowie, Fiona (Blackwell Pub., 2006)
"The second edition of this popular introduction to the anthropology of religion now features new chapters on mythology and pilgrimage, as well as coverage of topics such as religious syncretism and urban legends." "This accessible textbook will inspire students to explore the field further and encourage them to see that anthropology is not just about reading or doing fieldwork, but offers an enriching way of looking at the world."--BOOK JACKET.